Actualización diagnóstica-microbiológica de la Tuberculosis pulmonar - Hernán Sebastián, Flores Claudio (2021)
The present bibliographic review project has the general objective of compiling information on the microbiological diagnostic updates of pulmonary tuberculosis, to carry out this project it based clearly on the use of search engines such as Google Scholar, Scielo, PubMed, Scopus, Lilacs and Redalyc where it was possible to collect various scientific articles related to the subject of the project, applying various inclusion and exclusion criteria such as the year of publication of the article to only select those articles with the most current information possible. Among the diagnostic updates for this pathology there were automated methods, mycobacteriophages, immunochromatographic tests and molecular tests, the latter being the most used method to diagnose pulmonary tuberculosis in the most vulnerable groups such as people with the human immunodeficiency virus (HIV) and people in conditions overcrowding. The main advantage of current diagnostic methods for this pathology in comparison with conventional methods is the short time in which results can be obtained, this is very convenient since the main method to be able to contain the spread of contagious diseases such as pulmonary tuberculosis relies heavily on prompt diagnosis and treatment.